Once again about COVID-19 (clinical lecture) - Vladimir V. Borisov (LLC "MEDIAFORMAT", 2022)
The paper summarizes current research data on the nature, spread, clinical course, pathogenesis of complications and sequelae of coVId-19. The developing cognitive disorders, erectile and endothelial dysfunctions, oxidative stress, and hormone imbalances are discussed. The role of using antioxidants, vitamins, and micronutrients for treatment and prevention of complications in patients with coVId-19 and post-coVId syndrome is clarified by the example of the Selzinc Plus premix.